Is a body mass index of less than 18.5 kg/m2 associated with an increased susceptibility to mild cognitive impairment? A cross-sectional study conducted in China - Wei Li; Ling Yue; Shifu Xiao; Lin Sun (BMJ Open)
Objective Investigating the correlation between body mass index (BMI) and cognitive decline among elderly people in the Chinese community.Design A non-random sampling method was employed to conduct a cross-sectional, mixed methods survey among elderly individuals in the Chinese community.Setting This research was conducted across the country, focusing on 20 distinct communities (2 rural and 18 urban) situated in the eastern, central and western parts of China.Participants The China Longitudinal Aging Study (cohort 1) and Shanghai Brain Aging study (cohort 2) were the sources of the present data. Cohort 1 consisted of 2947 individuals aged 60 and above, who were subjected to a comprehensive screening procedure encompassing a physical examination, medical background and initial evaluations of cognitive abilities through an in-person interview. Cohort 2 comprised an extra 226 older adults, including 54 patients with mild cognitive impairment (MCI) and 174 normal adults, and unlike cohort 1, all of them underwent T1 phase MRI scans.Outcome measures The cognitive abilities, BMI and structural magnetic resonance properties of elderly individuals in the Chinese community.Results In cohort 1, we discovered that having a BMI below 18.5 kg/m2 posed a significant risk for MCI (p=0.005, OR=2.000, 95% CI: 1.228 to 3.255), regardless of age, gender and other significant variables. Despite this, there was no correlation between dementia and various BMIs. In cohort 2, we found that both left and right hippocampal volumes were significantly smaller in patients with MCI than in normal older adults, and there was a clear mediating effect between the right hippocampus, BMI and cognitive impairment (r=2.182, p=0.030).Conclusions BMI below 18.5 kg/m2 is associated with an increased likelihood of mild cognitive decline, which may be related to the effect of BMI on the volume of the right hippocampus.